Computer simulation of the stochastic dynamics of super-paramagnetic particles in ferrofluids - Scherer, Claudio (2013)
Several papers have been written on the complex problem of the stochastic dynamics of the magnetic moments of super-paramagnetic particles, simultaneously with the stochastic rotation of these colloidal particles in a ferrofluid [1–3]. None of these works, however, is sufficiently general and conveniently simple and clear to be used in sumulational works to appropriately describe the experimental super-paramagntetic resonance lines. We have a new proposal for the equations of rotational motion, which is appropriate for simulations. Those equations are stochastic differential equations with multiplicative noise. Therefore, they have to be interpreted as Stratonovich-Langevin equations and the roles of stochastic calculus have to be used in the simulations. For this reason we will briefly present the essence of the numerical algorithms used in the solutions of Stratonovich equations. Finally, the simulational results for the magnetic response functions, and the corresponding dynamic susceptibilities, will be shown and their consequences will be analyzed.